Identification of two major quantitative trait locus for fresh seed dormancy using the diversity arrays technology and diversity arrays technology‐seq based genetic map in Spanish‐type peanuts. Issue 3 (12th April 2016) - Vishwakarma, Manish K; Pandey, Manish K; Shasidhar, Yaduru; Manohar, Surendra S; Nagesh, Patne; Janila, Pasupuleti; Varshney, Rajeev K
Abstract: Seed quality for both germination in the next generation and for human consumption is adversely affected due to preharvest sprouting in peanut. It also makes seeds more vulnerable to infection by a number of pathogens. Therefore, it is desirable to have 2–3 weeks of fresh seed dormancy (FSD) in the peanut varieties. In this context, one F2 population was developed from a cross between non‐dormant (ICGV 00350) and dormant (ICGV 97045) genotypes. Phenotyping of this population showed control of the trait by two recessive genes. In parallel, genotyping of the population with Diversity Arrays Technology (DArT) and DArT‐seq markers provided a genetic map with 1152 loci covering a map distance of 2423.12 cM and map density of 2.96 cM/loci. Quantitative trait locus (QTL) analysis identified two major QTLs, namely qfsd‐1 and qfsd‐2 explaining 22.14% and 71.21% of phenotypic variation, respectively. These QTLs, after validation in different genetic backgrounds, may be useful for molecular breeding for FSD in peanut.